A EURASIAN ISLAM? (A vision on the position and evolution of Islam and Islamism in former Soviet Central Asia and the Caspian) - DE CORDIER, Bruno (CENTRAL ASIA AND THE CAUCASUS, 2008)
Scenarios of “balkanization,” “Talibanization” and “revolutionary contamination from Iran” of the southern Soviet rim were popular in the early 1990s. These concerns were understandable since they came at times when the world was simultaneously confronted with nationalist wars in the Balkans, the appearance of several newly independent states with Muslim majorities in the former Soviet space and the outbreak of a number of armed conflicts in this part of the world (Tajikistan, Nagorno-Karabakh), the first Gulf war as well as Islamist movements turning seriously wrong in Afghanistan and Algeria. Reality turned out to be more complex. The purpose of this article is to tackle a number of conventional truths about Islam in the region and to point out certain sociological factors which, in my opinion, will determine the evolution of Islam and Islamism in former Soviet Central Asia and the Caspian In this analysis, I define the region as a space with six states that emerged from the U.S.S.R. and where the majority of the population is, at least nominally or traditionally, of the Islamic faith: Ka zakhstan, Uzbekistan, Kyrgyzstan, Tajikistan, Turkmenistan and, on the other side of the Caspian, Azerbaijan. In average, in 2004, 80 percent of the population in this region was or is at least considered to be Muslim.1 The large majority of the 52.3 million Muslims in the region, historically known as Turkistan, are of Hanafi Sunni tradition.2 Certains micro-regions and communities are of Chafii Sunni tradition (in some parts of Tajikistan and Azerbaijan notably) while there are Twelver Shi‘ites (a two-thirds majority in Azerbaijan, a substantial minority in Uzbekistan) as well as Ismaili Shi‘ites (in the eastern part of Tajikistan).3 The earlier use of the expression “nominally or traditionally of the Islamic faith” is not at random. This is a part of the Islamic world where the position and practice of Islam developed along different lines than those in “classical” Islamic countries. So what are the main characteristics of Islam in this space?